Structural modification of regenerated fuller earth and its application in the adsorption of anionic and cationic dyes (2015)
Fuller's earth is an inorganic material used in the electric industry for dielectric oil regeneration. After decontamination treatment, Fuller's earth is regenerated and reused. In this study, the removal capacity of regenerated Fuller for the treatment of water contaminated with dyes of different nature and in turn, how this capacity can be increased by structural modification of the material was evaluated. Thus, the regenerated Fuller earth without any modification reached 99% removal of methylene blue. However, for treatment of effluents contaminated with red 40, acid and thermal modification of material was required to obtain adsorption greater than 94% of the dye. In conclusion, regenerated Fuller earth adsorbent is suitable for treating effluents contaminated with cationic coloring materials. However, removal of anionic dyes is not efficient, the structural modification of the material to be necessary to enhance the removal of these type colorants.